2022
DOI: 10.1177/0308518x211072545
|View full text |Cite
|
Sign up to set email alerts
|

A very British state capitalism: Variegation, political connections and bailouts during the COVID-19 crisis

Abstract: The COVID-19 pandemic has resulted in governments playing increasingly prominent roles as active economic agents. However, state capitalism does not necessarily serve broad developmental purposes, and rather can be directed to supporting sectional and private interests. As the literature on variegated capitalism alerts us, governments and other actors regularly devise fixes in response to a systemic crisis, but the focus, scale, and scope of the interventions vary considerably, according to the constellation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Some of the socio-spatial relations that have been investigated – and will undoubtedly continue to yield fresh insights into the polymorphous geographies of contemporary state capitalism – include Sperber's (2022) complex relational geographies of social class undergirding state capitalism; political connections between state and business elites ( Wood et al, 2023 ); geopolitics ( Kinossian and Morgan, 2023 ; Ward et al, 2023 ); social relations of production and labor transformations ( Alami and Dixon, 2023 ); relations of empire ( Eagleton-Pierce, 2023 ; Silverwood and Berry, 2023 ; Whiteside, 2023 ); territorial relations at a range of scales ( Su and Lim, 2023 ); networks of production ( McGregor and Coe, 2023 ); corporate ownership ( Babić, 2023 ; Babic et al, 2020 ; Haberly and Wójcik, 2017 ); and finance ( Hall, 2023 ; Petry et al, 2023 ; Sokol, 2023 ). There is also considerable scope for further expanding the socio-spatial relations under consideration in state capitalism research, as some recent contributions have creatively shown (e.g.…”
Section: Centring Relationality In the New State Capitalismmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the socio-spatial relations that have been investigated – and will undoubtedly continue to yield fresh insights into the polymorphous geographies of contemporary state capitalism – include Sperber's (2022) complex relational geographies of social class undergirding state capitalism; political connections between state and business elites ( Wood et al, 2023 ); geopolitics ( Kinossian and Morgan, 2023 ; Ward et al, 2023 ); social relations of production and labor transformations ( Alami and Dixon, 2023 ); relations of empire ( Eagleton-Pierce, 2023 ; Silverwood and Berry, 2023 ; Whiteside, 2023 ); territorial relations at a range of scales ( Su and Lim, 2023 ); networks of production ( McGregor and Coe, 2023 ); corporate ownership ( Babić, 2023 ; Babic et al, 2020 ; Haberly and Wójcik, 2017 ); and finance ( Hall, 2023 ; Petry et al, 2023 ; Sokol, 2023 ). There is also considerable scope for further expanding the socio-spatial relations under consideration in state capitalism research, as some recent contributions have creatively shown (e.g.…”
Section: Centring Relationality In the New State Capitalismmentioning
confidence: 99%
“…In ‘A very British state capitalism’, Wood et al (2023) argue that the uneven distribution of COVID-19 financial assistance across regions and sectors has exacerbated spatial variegation and unequal territorial outcomes in the British variant of state capitalism. Their study of the granting of government bailouts and contracts emphasizes the significance of both sectoral concerns and political connections, and shows that the British case offers a peculiar combination of features traditionally associated with different varieties of capitalism (crony, liberal and state capitalism).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The post-2008 global political economy, with its once-in-a-generation state maneuvers to rescue capitalism through market intervention, bailouts and asset taking, was seen by some to represent a break with earlier trends of neoliberal laissez-faire and privatization when, for example, states moved to hold minority and majority shares in financialized enterprises and to wield influential sovereign wealth funds (Musacchio and Lazzarini, 2014). Following this account, the arrival of yet another pattern-altering crisis – the 2020 global pandemic and subsequent lockdowns affecting global production, circulation, exchange and social reproduction – has not only reinforced a number of post-2008 trajectories in state-capitalist restructuring (Wood et al, 2023), it seems also to have propelled new waves of populism, neomercantilism and myriad other signifiers of highly politicized monetary, fiscal, trade and industrial policies (cf. Petry et al, 2023 on neoliberalism vs. state capitalism).…”
mentioning
confidence: 99%
“…Variously centred on Jessop's strategic-relational approach (Paul and Cumbers, 2023; see also Jessop, 2002; Jessop and Morgan, 2022), Hart's relational-comparative approach (Meulbroek, 2023) and Schering's model of the accumulative state (Silverwood and Berry, 2023; see Scheiring, 2020), established theories are mobilized and blended in novel ways. The authors apply theoretical insights to the logics, drivers and features of contemporary state capitalism (Alami and Dixon, 2023; Palcic et al, 2023; Paul and Cumbers, 2023; Wood et al, 2023), histories and temporalities that complexify otherwise received periodizations (Alami and Dixon, 2023; Eagleton-Pierce, 2023; Palcic et al, 2023; Silverwood and Berry, 2023), and directly address the capitalist state in state capitalism (Alami and Dixon, 2023; Palcic et al, 2023; Su and Lim, 2023). Rather than positioning established political economy theories of the capitalist state in conflict or tension with the upstart literature on the new state capitalism, the papers in the theme issue push for new directions in theory and revised readings of the new state capitalism.…”
mentioning
confidence: 99%